MUSICAL PERFORMANCE OF MAPPADENDANG HARVEST RITUAL IN BUAE VILLAGE SIDENRENG RAPPANG REGENCY SOUTH SULAWESI - Fardian, Fardian; Sedana, I Nyoman; Ardini, Ni Wayan; Sudirana, I Wayan (UPT Pusat Penerbitan LP2MPP ISI Bali, 2024)
People in Buae village, Sidenreng Rappang, South Sulawesi, annually perform the Mappadendang harvest ritual to express gratitude for a successful rice harvest. This research aims to discuss the unique musical behavior of the community during the Mappadendang process, namely singing Sure' “Meong Palo Karellae”, and drumming “Lesung”. This research uses a qualitative design with an ethnomusicology approach. The author obtained research data through field observations, interviews, and documentation. The collected data were analyzed using the flowchart technique: data reduction, display, and conclusion/verification. The results showed that Mappadendang music performances are related to spiritual, social, and entertainment functions. Mappadendang musical performances produce musical activities based on local wisdom creativity, including 1) Massure', which is the process of singing the text of “Meong Palo Karellae” with a vocal style produced in mono melodic form, played based on the interpretation of Passure' (Lontar Reader) tones. In Lesung drumming, the rhythm of Mappadendang is related to the concept of Sulapa Eppa'. Two rhythmic patterns are found: 1) “Manganak” is a pattern played by “Indo' Padendang” (female player), resulting in a four-beat interweaving played alternately and repeatedly. 2) “Mattang” is the rhythmic pattern played by “Ambo' Padendang” (male player), who plays contrasting rhythmic patterns, tending to produce synchronized rhythmic forms. The results of this research are significant because they reflect the community's views towards the sustainability of Mappadendang. Readers will know the uniqueness of Mappadendang music performance, which can inspire the creation of new art based on local wisdom.